The GABAAα5-selective Modulator, RO4938581, Rescues Protein Anomalies in the Ts65Dn Mouse Model of Down Syndrome. (21st February 2018) - Block, A.; Ahmed, Md.M.; Rueda, N.; Hernandez, M.-C.; Martinez-Cué, C.; Gardiner, K.J.
Highlights: Levels of 91 proteins relevant to brain function were measured in Ts65Dn hippocampus after training in the Morris Water Maze. Levels of 55 proteins/protein modifications were abnormal in vehicle-treated Ts65Dn compared with littermate controls. The GABAAα5-selective modulator, RO4938581, that rescues learning deficits, corrected the majority of protein abnormalities. Protein abnormalities, and their correction, are consistent with abnormalities in and rescue of LTP. Abstract: Down syndrome (DS), trisomy of human chromosome 21 (Hsa21), is the most common genetic cause of intellectual disability (ID). There are no treatments for the cognitive deficits. The Ts65Dn is a partial trisomy mouse model of DS that shows learning and memory (LM) impairments and other abnormalities relevant to those seen in DS. Many drugs and small molecules have been shown to rescue the LM deficits, but little is known about the associated molecular responses. Here, patterns of protein expression are described in hippocampus of Ts65Dn and euploid littermate controls exposed to a battery of LM and behavior tests with and without chronic treatment with the GABAA receptor α5 subunit-selective negative allosteric modulator, RO4938581, that rescued LM deficits. Levels of 91 proteins/protein modifications, selected for relevance to LM and synaptic plasticity, were measured: 44 of 52 abnormalities present in vehicle-treated Ts65Dn were corrected by RO4938581. Superimposing protein data onto the molecular pathway defining long-term potentiation (LTP) shows that profiles are consistent with both abnormal LTP in vehicle-treated Ts65Dn and its observed rescue by RO4938581. Lastly, comparing these results with those from Ts65Dn treated, using a different protocol, with the NMDA receptor antagonist, memantine, that also rescues LM impairments, identifies common and divergent responses to the two drugs. Expansion of this approach to include additional drugs and DS models would aid in determining critical protein abnormalities and in identifying cocktails of drugs and/or new drug targets that would be effective in clinical trials for ID in DS.